Decoupled, Disturbance Rejection Control for A Turbocharged Diesel Engine with Dual-loop EGR System. Issue 11 (2016) - Chen, Song; Yan, Fengjun
Abstract: Dual-loop exhaust gas recirculation (EGR) with variable geometry turbocharger (VGT) provides a flexible architecture for achieving desired intake manifold conditions, including temperature, pressure and oxygen concentration, which are critical for advanced combustion mode control in modern engines. However, the highly nonlinear system dynamics and strong coupling effects between loops make the widely used, control oriented model failed to trace the system states well, especially in transient situations. This paper presents a control method for this nonlinear, multi-input multi-output (MIMO) system with the compensation for modeling error and disturbance. By taking both the advantages of the knowledge of system dynamics and the idea of disturbance rejection, the modified active disturbance rejection control (ADRC) with extended states observer (ESO) was utilized to achieve such a control objective. Here, the term "disturbance" lumps all the internal and external errors, including the modeling errors and coupling effects. By actively estimating the disturbance and compensating its effects, the intake manifold conditions can be controlled in a decoupled fashion. The proposed method was validated through high-fidelity GT-Power model simulations.